DEVELOPMENT LEARNING MATERIAL ESP - Fadhliyah, Muin Rahma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
One of the aspects of teaching ESP is development materials. ESP teaching should be linked to a specific discipline, make use of methodology that differs from that used in English for General Purpose teaching. They assert that it is essential that an ESP course take into consideration register, genres and associated language that students need to understand and to manipulated in order to carry out activities related to their disciplines.